Inhibition of HMGB1 Promotes Osseointegration under Hyperglycemic Condition through Improvement of BMSC Dysfunction. (20th December 2019) - Liu, Beilei; Gan, Xueqi; Zhao, Yuwei; Yu, Hongdou; Gao, Jing; Yu, Haiyang
Abstract : High mobility group box 1 (HMGB1) participates actively in oxidative stress damage and the latter relates closely to diabetic complications, including poor implant osseointegration. This article is aimed at investigating the effects of HMGB1 on dysfunction of bone marrow stromal cells (BMSCs) and impaired osseointegration under diabetic environment. In vitro, BMSCs were treated with normal glucose (NG), high glucose (HG), and HG+glycyrrhizin (HMGB1 inhibitor, HG+GL). Cell proliferation, osteogenic behaviors, and oxidative stress were determined. In vivo, 8-week-old Sprague-Dawley rats were categorized to control, streptozotocin-induced diabetic, and diabetic-GL groups. Rats received GL (50 mg/kg, i.p.) or vehicle treatment daily after titanium implants were planted into the tibiae. After 4 and 8 weeks, plasma lipoperoxide detection, μ CT analysis, and histomorphometric evaluation were conducted. By these approaches, we demonstrated that inhibiting HMGB1 by GL significantly attenuated HG-induced upregulation of HMGB1, HMGB1 ligand receptor for advanced glycation end products (RAGE) and their interaction, relieved oxidative stress, and reversed the downregulation of osteogenic markers, resulting in improved osteogenic differentiation. In diabetic rats, GL administration suppressed the upregulation of HMGB1, attenuated the lipoperoxide, and ameliorated the impaired trabecular structure and osseointegration. Taken together, inhibiting HMGB1 can be an effective approach to relieve BMSC dysfunction and enhance osseointegration under diabetic environment.